MINUMAN PROBIOTIK DARI BEBERAPA JENIS KULIT BUAH PISANG DENGAN VARIASI INOKULUM Lactobacillus casei - Eny Idayati; Rikka W. Sir; Senni J. Bunga (Partner, 2009)
Probiotic beverages were made from banana peels that inoculated bacteri Lactobacillus casei. The aims of this research was to study effect of kind of banana peels and concentration of inculant on quality of beverage. This research used completely random design, with combination of two factors that were kinds of banana peels (keprok, susu and ambon) and concentration of inoculant (4%, 5%, 6%, 7%, and 8% in milk media) in three times. Protein and calsium content were measured as well as acidity (pH). Sensoric method was used for determining organoleptic properties (flavour, color, texture, taste). Data was analyzed using ANOVA, followed LSD test in 0,05 level. Result showed probiotic beverage fromâ€susuâ€ peel that inoculated Lactobacillus casei concentration 8% (K2S5)Keywords : probiotic, beverages, banana peels,Â  Lactobacillus casei